2019
DOI: 10.1111/nep.13265
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of dengue fever and its impact on renal function in renal transplant recipients and patients with chronic kidney disease

Abstract: Clinical features of dengue fever were different in renal transplant recipients and patients with CKD. Severe worsening of renal function was common in CKD patients. Worsening of renal function in renal transplant recipients was less severe and transient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…Pathophysiological consequences of dengue infection, especially plasma leakage leading to reduced intravascular volume could aggravate already compromised renal function and would challenge fluid and electrolyte management, not only in patients with CKD but also in those with CHF. 30 The analysis, contrary to expectations, did not find an association between chronic hepatitis and the adverse outcomes that we explored. Elevations in hepatic transaminases and acute hepatitis frequently occur during acute dengue, to the point that acute liver failure in dengue has been managed with liver transplantation.…”
Section: Discussioncontrasting
confidence: 84%
“…Pathophysiological consequences of dengue infection, especially plasma leakage leading to reduced intravascular volume could aggravate already compromised renal function and would challenge fluid and electrolyte management, not only in patients with CKD but also in those with CHF. 30 The analysis, contrary to expectations, did not find an association between chronic hepatitis and the adverse outcomes that we explored. Elevations in hepatic transaminases and acute hepatitis frequently occur during acute dengue, to the point that acute liver failure in dengue has been managed with liver transplantation.…”
Section: Discussioncontrasting
confidence: 84%
“…Patients with Chronic Kidney Disease (CKD) are also at an increased risk of severe DF or mortality. DF often causes acute kidney injury due to the hemorrhagic shock state, rhabdomyolysis and glomerulonephritis that can be produced by the virus, thus, patients with CKD are more prone to that kidney damage (Mallhi et al, 2017b;Thomas et al, 2019). Other pathophysiological mechanism that can explain this risk in patients with CKD can be secondary to inadequate production of immune mediators by infected mononuclear cell, (Lee et al, 2019) As for the increased risk associated with young age, compared to adults, children are more prone to vascular fragility and reduced capillary perfusion, predisposing them to plasma leakage, hemoconcentration and thrombocytopenia, reflecting low volume status (Lovera et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The few available studies suggest that the initial symptoms of dengue-infected transplant recipients is identical across cases. 8,9 A systematic review from 2017 found a higher incidence of severe dengue fever and a higher mortality rate (of up to 8.9%) in patients who contracted the virus through transplantation. 10 The review also found that more than 60% of transplanted patients had transient renal dysfunction, and 6.5% had graft loss.…”
Section: Discussionmentioning
confidence: 99%